Researching social inclusion in student mobility: methodological strategies in studying the Erasmus programme - Cairns, D. (International Journal of Research and Method in Education, 2019)
This article explores different methodological approaches to the study of social inclusion in the European Commission’s Erasmus undergraduate exchange programme, elaborating upon the approach taken in a study of Erasmus conducted in Portugal. The opening section of the discussion acknowledges the prior tradition of quantitative research on student mobility in Europe as a means of providing indicators of programmatic success to policymakers and stakeholders, and the existence of micro level studies that examine specific aspects of the Erasmus experience such as the emergence of shared European identities and building work competencies. What these approaches share is an emphasis on student perspectives: learning about the impact of exchange visits from past participants. As an alternative approach, I have focused on the institutional level of the programme, using qualitative interviews with individuals involved in managing Erasmus mobility at a diverse range of universities, an approach that I argue unlocks valuable knowledge about issues such as social inclusion within the programme.